Influence of plant growth promoting rhizobacteria on fruit yield, pomological characteristics and chemical contents in cucumber mosaic virus-infected tomato plants - DASHTI, NARJES H.; MONTASSER, MAGDY S.; ALI, NEDAA Y. A.; CHERIAN, VINEETHA M. (Kuwait Journal of Science, 2014)
The influence of two plant growth promoting rhizobacteria (PGPR) strains, Pseudomonas aeruginosa and Stenotrophomonas rhizophilia, on fruit yields, pomological traits and chemical contents on cucumber mosaic virus (CMV) infected-tomato (Solanum lycopersicum) fruits were studied. Two CMV strains were used to infect tomato plants. CMV-KU1 is a locally isolated CMV associated with a benign viral satellite RNA, while CMV-16 is a satellite-free virus that causes severe stunting, manifested by vegetative and fruit yield loss in tomato. The study was conducted in parallel on two different cultivar varieties of tomato, namely Supermarmande and UC82B and results obtained for each were compared. The results indicated that the presence of the PGPR almost doubled the average yield per plant, even of those plants infected by the CMV viruses, compared to the healthy control treatments. There was also a significant improvement in the pomological qualities of the PGPR-treated tomato fruits compared to the corresponding healthy and virus infected treatments, especially, in the average of weight, hight and volume of fruits. The chemical analysis of tomato fruits revealed that the presence of the PGPRs increased the total protein, lycopene, alkalinity and phenol content of the tomato fruits compared to the healthy controls. However, PGPRs had no influence on reduced sugars, total soluble solids or the titerable acid content, but reduced the amount of ascorbic acid in tomato fruits of infected plants compared to healthy controls.